An investigation of clemency and pardons in death penalty cases in Southeast Asia from 1975-2009 - Pascoe, D; Daniel Pascoe (2013)
Four of the contemporary practitioners of the death penalty in Southeast Asia: Indonesia, Malaysia, Thailand and Singapore, performed judicial executions on a regular basis between the years 1975 and 2009. Notwithstanding this similarity, the number of death sentences passed by courts that were subsequently reduced to a term of imprisonment through grants of clemency by the executive (or where the prisoner sentenced to death is exonerated by way of a pardon) varied remarkably between these jurisdictions over this 35-year period: some of these countries commuted the sentences of death row prisoners often, others rarely. In this DPhil thesis, I employ the methodology of comparative criminal justice to explore the discrepancies and similarities in capital clemency practice between these four Southeast Asian jurisdictions, seeking to document the known examples of clemency grants over the course of their modern history, and to investigate the reasons why retentionist countries exercise clemency at vastly different ‘rates’ in finalised capital cases. As clemency and pardon deliberations by the executive are usually performed in secret, academic study of the subject has remained scarce, and the suspected reasons behind death sentence commutations, and their relative frequency, are rarely analysed. My inductive, qualitative study in comparative criminal justice will attempt to address these deficiencies in analysis as they apply to four Southeast Asian countries that continue to practice capital punishment as a form of criminal sanction. Moving beyond Amnesty International’s simplistic observation that ‘nowhere in Asia has the ready availability of such clemency been marked’, I examine the intricacies of the clemency practice in each jurisdiction, and arrive at regional trends and patterns.